Structuring axes of primary health care for children: an integrative review (Research, Society and Development, 2020)
Objective: To synthesize the evidence of the presence and extent of the attributes of primary care in child health in Brazil. Method: Integrative literature review using PubMed, Lilacs and SciELO databases. We searched for original articles available for free in full, published since 2002 in Portuguese, English and Spanish, which used the Primary Care Assessment Tool with users who are caregivers of children up to 9 years old. The nine selected articles were analyzed using a previously prepared form. Results: Among the selected articles, all were published in Brazilian journals and come from research conducted in Brazil. Of the seven articles that presented the general score of primary health care in children's health, only one scenario was found with strong guidance, but with borderline score (6.6). Conclusion: The evaluation of primary health care based on its organizing attributes is a valuable tool for the management of health services, however, the studies analyzed show that, from the point of view of the user (caregiver), the services that they provide assistance to children, especially in the Brazilian scenario, they are not oriented towards primary care. Thus, the need to rethink the structure and processes involved in this field is evident.